Perbaikan Faktor Daya Dengan Implementasitriac Berbasis Mikrokontroller Pada Jaringan Tiga Fasa Seimbang - Nico Latino; Amir Hamzah (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The need for good power quality is very important. The good power quality is thepower factor can reach 0.85 up to 1 and it will improve power capacity, and energyefficiency. In common, Because the inductive load of PLN customers, power factor turnbelow 0.85. To Increase the power quality, it is necessary to install capacitors based on load,poor power factor need more capasitors. The capasitors are connected to system trough asoft switch by using TRIAC to reduce inrush current that happen with contactor switch.The power factor corrector circuit are consist of phase detector, zero crossing detector,and XOR logic gate used for produce the phase angle that feed to Arduino input for readingthe value of power factor. Then in Arduino will process the input to TRIAC for set up certainpulse that trigger firing angle in order to control the duty cycle on TRIAC. Firing angle canbe vary based on the quality of power factor.Keywords: Power factor, capasitor, arduino, TRIAC, duty cycle